Design and Optimization of Simvastatin Self-Microemulsifying Drug Delivery System for Enhanced Therapeutic Potential - Kumar, Ashish (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: In present study, a self-microemulsifying drug delivery system (SMEDDS) has been developed and optimized to enhance solubility and bioavailability of poorly water soluble drug simvastatin. Material and Methods: Phase solubility studies and emulsification tests were performed for selection of a suitable oil, surfactant, and co- solvent. A three factor, two level, mixture design of experiments was used to optimize the concentration of components for SMEDDS formulation for achieving excellent physicochemical properties such as small globule size (<150 nm) and high dissolution (more than 85% of drug released within 15 min). Lipolysis of optimized simvastatin loaded SMEDDS formulation by pancreatic lipase was done to investigate effect on solubilizing capacity of dispersed colloid in aqueous phase. Pharmacodynamic study on hyperlipidaemic rats models was done to investigate bioavailability of optimized simvastatin loaded SMEDDS formulation in comparison to pure drug. Result and Discussion: The optimized Simvastatin loaded SMEDDS formulation containing 10.0% w/w Capmul PG8(oil), 30.0% w/w Koliphore EL(surfactant) and 60.0% w/w Transcutol (co-solvent) shows smallest globule size (22.02nm) and maximum drug release (98.9% in 15 minutes). Lipolysis of optimized simvastatin loaded SMEDDS formulation showed that nature of colloidal species changed during lipolysis process does not affect solublizing capacity of dispersed colloid in aqueous phase. Pharmacodynamic investigation on hyperlipidaemic rats models reveals that optimized simvastatin loaded SMEDDS formulation significantly reduced serum lipid levels when compared with Simvastatin drug and hence indicating improved bioavailability. Conclusion: These results suggest that the Mixture response surface design could be a suitable approach for optimizing Simvastatin SMEDDS formulation variablesKey words: Bioavailability, design of experiment, dissolution, globule size, lipolysis